The diversity of indoor airborne molds growing in the university libraries in Indonesia - RAHMAWATI RAHMAWATI; LANGKAH SEMBIRING; LATIFFAH ZAKARIA; ENDANG S. RAHAYU (Biodiversitas Journal of Biological Diversity, 2018)
Rahmawati, Sembiring L, Zakaria L, Rahayu ES. 2018. The diversity of indoor airborne molds growing in the university libraries in Indonesia. Biodiversitas 19: 194-201. Airborne mold is potentially causing respiratory diseases. The aim of this study was to investigate the diversity of indoor airborne molds isolated from some libraries in Universitas Gadjah Mada (Gadjah Mada University), Yogyakarta, Indonesia based on morphological characteristics. Sampling was conducted in six libraries at Universitas Gadjah Mada (Libraries of Food and Nutrition at Inter-University Center or Pusat Antar Universitas (PAU), Biotechnology at PAU, Faculty of Biology, Faculty of Mathematics and Natural Sciences, Faculty of Master of Management, and Faculty of Geography) by non-volumetric air sampling method. Isolation of indoor airborne molds was conducted by using two petri dishes containing Dichloran 18% Glycerol Agar (DG 18) for each room. Morphological identification of isolates of indoor airborne molds was based on macromorphological and micromorphological characteristics. Isolation and identification were conducted in Laboratory of Microbiology of Food and Nutrition of PAU at Universitas Gadjah Mada. The result showed the diversity of indoor airborne molds, identified to be members of genera Alternaria, Aspergillus, Aureobasidium, Byssochlamys, Cadophora, Chaetomium, Chrysonilia, Cladosporium, Curvularia, Emericella, Epicoccum, Eurotium, Fusarium, Geomyces, Mucor, Penicillium, Rhizopus, Rhizomucor, Stemphylium, Scopulariopsis, Wallemia, and Xeromyces. Members of genera Aspergillus, Cladosporium, and Penicillium were the most dominant molds. The results of this study indicate that the presence of molds potentially causes illness for the library users.